Degradation mechanism of flexible perovskite solar cells: Investigated by tracking of the heterojunction property. (March 2020) - Wang, Minhuan; Feng, Yulin; Dong, Qingshun; Bian, Jiming; Ma, Congcong; Chen, Ransheng; Shi, Yantao
Graphical abstract: Flexible PSCs with impressive PCE and outstanding stability were achieved. A model based on the single heterojunction thin film solar cell was proposed to elucidate the irreversible degradation mechanism based on the evolution of the essential parameters. Highlights: F-PSCs with impressive PCE of 13.4% were achieved. The Cs0.05 (FA0.85 MA0.15 )0.95 Pb(I0.85 Br0.15 )3 perovskite layer was deposited. The unencapsulated F-PSCs can maintain 80% of its initial value after 150 days. A model was employed to clarify the degradation mechanism. The mechanism was elucidated based on the evolution during the aging process. Abstract: Flexible perovskite solar cells (F-PSCs) with impressive power conversion efficiency (PCE) of 13.4 % were achieved on ITO/PEN substrate, where the high quality perovskite light harvesting layer with the composition of Cs0.05 (FA0.85 MA0.15 )0.95 Pb(I0.85 Br0.15 )3 was achieved by the well-established anti-solvent spin-coating method in our group. The unencapsulated F-PSCs can maintain 80 % of its initial value after 150 days exposed to ambient environment, the outstanding stability was among the best shelf stability ever reported for F-PSCs. Remarkably, a model based on the single heterojunction thin film solar cell was employed to clarify the irreversible degradation mechanism of the F-PSCs based on the evolution of the essential parameters during the aging process, like the ideality factor (A), series resistance (Rs ) and the reverse saturated current density ( J 0 ). Our findings shed deep insight into the degradation mechanism of F-PSCs, and favorable for rational optimizing both the efficiency and stability of perovskite-based optoelectric device.